2020
DOI: 10.3390/machines8020024
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Motorcycle Steering Damper for a Safer Ride

Abstract: Powered-two-wheelers (PTWs) are increasingly popular because of their lower cost compared to cars, and therefore the riders’ exposure risk is increasing. Due to their complex dynamics characterized by high non-linearity and inherent instability, PTWs are more difficult to control compared to four-wheeled vehicles. Wobble is a high-frequency instability mode affecting the steering assembly of the PTW, and which often causes the rider to lose control and crash when it occurs. In this paper, we present the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In Equation ( 5), substituting the value of the d pm max to the d pm2 and the generic pitch diameter d pmi to the value of d pm1 , the trend of the axial displacement during the acceleration phase is obtained, as shown in Equation (6).…”
Section: Half-pulley's Axial Displacement Calculationmentioning
confidence: 99%
See 3 more Smart Citations
“…In Equation ( 5), substituting the value of the d pm max to the d pm2 and the generic pitch diameter d pmi to the value of d pm1 , the trend of the axial displacement during the acceleration phase is obtained, as shown in Equation (6).…”
Section: Half-pulley's Axial Displacement Calculationmentioning
confidence: 99%
“…This correlation is valid in the various engine rotational speeds. Therefore, having determined a relationship between the belt position and the moveable half-pulley, it is possible to relate the roller's position to the belt's one, deploying Equation (6).…”
Section: Kinematic Analysis Of the Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this study and others found in literature, MR fluids present the problem that their magnetic particles tend to precipitate after long periods of inactivity. Piantini et al [9] conducted a similar study but applied to a motorcycle. In that case MR fluids also presented a good performance as a working fluid in a suspension system.…”
Section: Introductionmentioning
confidence: 99%